TRAUMA HEALING PADA PEREMPUAN KORBAN PLECEHAN SEKSUAL VERBAL (CATCALLING) - Yaya, Nani Alaniah; Fitriyani, Nina (Universitas Pahlawan Tuanku Tambusai, 2023)
Sexual harassment is increasingly prevalent in society by exposing various forms of sexually debilitating acts committed by men against women. The forms of sexual harassment experienced by women are not always in non-verbal forms but also in verbal forms. Verbal harassment is perpetrated by men in public spaces such as on the side of the road or in places where men usually gather. The purpose of this research is to find out